THE DEFINING FEATURES OF SOFT POWER STRATEGY IN GERMAN FOREIGN POLICY - Rustamova, L. R. (Vestnik MGIMO-Universiteta, 2016)
The defeat in the Second World War made Germany very carefully select the foreign policy concepts, which is still actual for the country. Until now, any political idea, even an indirect indication to the desire to establish German hegemony, could cause the deterioration of relations with partners in the EU and other neighboring countries. In these circumstances, Germany has chosen as the most appropriate foreign policy strategy for the promotion of the national interests the use of so-called "soft power" - the ability to encourage others to do what you want with the help of appeal, rather than through the manipulation of material needs. Germany has a large number of resources to implement the policy of "soft power." The German non-governmental organizations, political foundations are making a great contribution to make foreign policy attractive and spread political values. Organizations involved in exchange programs, scientific cooperation contribute to the expansion of German language and culture. A distinctive feature of German "soft power" organizations is that, despite the financing from the state, they retain the civilian nature of their activities, which is a necessary condition for the successful application of the concept. Another feature of German "soft power" is that its resources are directed not only at foreign audiences, but also German citizens. The key tasks of German soft power concept are to build a positive image of the country, to change its international legal status and to play the leading role in the EU.